The Effect of Uncertainty Training on the Improvement of Diagnostic Ability in Chinese Medical Students - Xiaomeng Xia; Yi Zeng; Pixiang Pi; Xianqing Wu; Xiaoling Fang; Jianlin Chen; Yan Zhong (Journal of Medical Education and Curricular Development, 2024)
Objective To evaluate the effect of the uncertainty training on improvement of students’ diagnostic ability. Methods Data were collected on 70 fifth-year medical students enrolled in the Case Discussion courses on Obstetrics and Gynecology in the spring of 2020. Of these students, 36 were in the uncertainty training group and 34 in the control group. The effect of training was evaluated by cognitively diagnostic assessment which mapped exam questions to 4 attributes assessing clinical reasoning and basic science knowledge. Results Uncertainty training was able to improve students’ ability to use basic science concepts for inference and problem solving, and the ability to integrate complex clinical information to arrive at a diagnosis. But it could not improve students’ ability on the basic recall of foundational concepts and the ability to use basic science concepts in clinical reasoning. Medical students could do well in integrating complex clinical information although they didn’t recall basic science knowledge well. Conclusion Uncertainty training could be used as an effective teaching method in Case Discussion course on Obstetrics and Gynecology. However, students still need to improve their basic knowledge besides the training.